Fritz Kreisler collection - Kreisler, Fritz, 1875-1962.; Lochner, Louis Paul, 1887-1975. (1845)
Holographs of original compositions, including sketches, transcriptions of other composers' music, manuscript and printed, correspondence, financial and legal documents, programs, clippings, photographs, and awards and honors. Includes papers of Kreisler biographer Louis Lochner: personal papers of Kreisler and material related to the biography.
Violinist and composer. Born in Vienna, international career.
Fritz Kreisler Collection, Music Division, Library of Congress.
Finding aid available in the Library of Congress Performing Arts Reading Room and on the Internet.
Keywords: Kreisler, Fritz, -- 1875-1962 -- Autographs; Kreisler, Fritz, -- 1875-1962 -- Correspondence; Violinists -- Autographs; Violinists -- Correspondence; Composers -- Autographs; Composers -- Correspondence